The Socio-Economic Impact of Inpres 1/2025 and Study Tour Prohibition on DIY Tourism - Haryanto, Eko; Tyas, Dyah Wahyuning; Noviati, Fitria (Institut Pariwisata dan Bisnis Internasional, 2025)
This study examines the socio-economic impacts of Presidential Instruction (Inpres) No. 1 of 2025 on budget efficiency and the Prohibition of Study Tours from West Java, Central Java, and DKI Jakarta on the tourism sector in the Special Region of Yogyakarta (DIY). The research aims to identify policy-induced changes, evaluate their effects on social and economic aspects, and propose mitigation strategies for industry stakeholders. Using a preliminary exploratory qualitative and quantitative analysis approach, the study finds that both policies have negatively affected DIY tourism. Specifically, the budget efficiency measures constrained local economic activities, while the study tour ban triggered a domino effect, reducing income for both formal and informal sector actors reliant on tourism. The findings highlight the need for nuanced policy implementation that balances efficiency with sustainable support for local economic growth.